Modern Characteristics Of International Educational Tourism - Jakhongirov Kamoliddin Asomiddin ugli (Genius Journals, 2024)
The article cites some of the definitions given by scholars of educational tourism. In the conditions of today's globalization, the characteristics of educational tourism as not only a type of tourist activity, but also as an important mechanism for managing the intercultural communication of peoples, as an effective way of implementing the principles of social partnership at the level of various subjects of interaction, are discussed. Also, the current trends in the development of educational tourism, the ranking of the world's best universities, and the analysis of the countries with the highest income from educational tourism are presented
Keywords: Globalization; Tourism; Excursion; Tourist Activity